2011
DOI: 10.1007/s11102-011-0330-3
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and acromegaly: a review

Abstract: To review the literature regarding the diagnosis and management of acromegaly during pregnancy. A systematic literature search was performed using MEDLINE including hand-searching reference lists from original articles. The diagnosis of acromegaly during pregnancy is made difficult due to the physiologic changes in pituitary GH secretion and IGF-1 production resulting from placental GH secretion and the inability of commercial assays to discriminate between pituitary and placental GH. Most patients with acrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 38 publications
(81 reference statements)
2
50
0
5
Order By: Relevance
“…As both acromegaly and pregnancy are associated with hypertension and diabetes, in uncontrolled acromegalic patients, pregnancy is reported to increase the prevalence of those comorbidities (2) and potentially complicate obstetrical/ fetal outcomes. In analogy to the effects of pregnancy on both tumoral (3) and nontumoral (4) lactotrophic cells, tumor enlargement and/or lactotrophic hyperplasia in acromegaly could also compress the optic chiasm and lead to visual impairment during pregnancy (5).…”
Section: Introductionmentioning
confidence: 99%
“…As both acromegaly and pregnancy are associated with hypertension and diabetes, in uncontrolled acromegalic patients, pregnancy is reported to increase the prevalence of those comorbidities (2) and potentially complicate obstetrical/ fetal outcomes. In analogy to the effects of pregnancy on both tumoral (3) and nontumoral (4) lactotrophic cells, tumor enlargement and/or lactotrophic hyperplasia in acromegaly could also compress the optic chiasm and lead to visual impairment during pregnancy (5).…”
Section: Introductionmentioning
confidence: 99%
“…If the tumor mass or the treatments do not destroy the gonadotropin lineage, the reproductive potential is preserved; however, fertility in patients with acromegaly is generally known to be impaired (7). Conceptions (spontaneous as well as induced) have been reported in less than 150 cases in the literature till date, achieved with and without treatment (4,5,7,8). GH and IGF-1 levels were not measured routinely in the patients in our study.…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that octreotide crosses placenta (21,22), and therefore, it may potentially affect the fetal outcome. Nevertheless, based on the lack of sufficient data on the safety of SAs during pregnancy, it is generally recommended to limit their usage during pregnancy in symptomatic patients (4). None of the five patients in our study were treated during pregnancy; while only two of them were receiving octreotide when they received the diagnosis of pregnancy, following which their medical treatment was discontinued.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations